Implementation of Human Resources Management (HRM) Towards Talent Management to Improve the Performance of Health Services at Jagakarsa Hospital - Rismanaadji, Rismanaadji; Farida Elmi (Dinasti International Journal of Digital Business Management, 2023)
This study aims to determine the Application of Human Resource Management (HRM) Towards Talent Management to Improve Health Service Performance at Jagakarsa Hospital. This research was conducted at the Regional General Hospital owned by the Provincial Government of DKI Jakarta in 2021. This type of qualitative research uses data collection methods by triangulating data with 5 (five) informants through interviews, observations and documents. The data were analyzed by the researchers themselves. The results showed that Jagakarsa Hospital had implemented human resource management in managing its employees while talent management had not been implemented. The advice given to Jagakarsa Hospital is to be able to accelerate the implementation of talent management to support health services to the community so that it has an impact on improving hospital performance. The acceleration activities include establishing policies related to the implementation of talent management in hospitals, forming a Hospital Talent Management Acceleration Team, compiling Standard Operating Procedures (SOP) regarding the Implementation of Talent Management at Jagakarsa Hospital.